Nursing Home Adoption of CDC and ASHRAE COVID-19 Built Environment Recommendations: A Characterization Study of Colorado Nursing Home Facilities. (October 2022) - Goldman, Cedra; Czaja, Christopher; Moses, X. J. Ethan; Van Dyke, Mike
Background: During the COVID-19 pandemic, the Centers for Disease Control and Prevention (CDC) and ASHRAE provided infection control recommendations for the built environments and ventilation systems of nursing homes (NHs). The level of adoption of the suggested strategies is unknown, as little information has been obtained from NHs identifying the strategies that were implemented. Objective: The primary goal of our study was to characterize the built environments of Colorado NHs during the COVID-19 pandemic to assess the level of adoption of CDC and ASHRAE recommendations. Our secondary goal was to identify opportunities and barriers that NHs face as they work to create health-protective built environments in the future. Method: We used the Nursing Home Built Environment survey to obtain data related to three main categories of CDC and ASHRAE recommendation for Colorado NHs: Resident Isolation, Improved Indoor Air Quality, and Staff Separation/Support. Results: Key findings included: (1) On average, NHs had 34% of their beds located in single-occupancy rooms; (2) seven (9%) NHs had designated COVID-positive "neighborhoods"; (3) 14 (20%) NHs had common area ventilation systems that were utilizing filters with a minimum efficiency reporting value 13 rating, or higher. Conclusion: Most Colorado NHs did not fully implement the COVID-19 built environment strategies recommended by CDC and ASHRAE. While there are barriers to the adoption of many of the strategies, there are also opportunities for immediate improvements that can support the health of vulnerable NH populations as we continue to see high rates of aerosolized infectious disease spread in NH facilities.